2022
DOI: 10.1002/jbm.a.37356
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of anti‐inflammatory lipid nanoparticles for mRNA delivery

Abstract: Lipid nanoparticles (LNPs) play a crucial role in delivering messenger RNA (mRNA) therapeutics for clinical applications, including COVID‐19 mRNA vaccines. While mRNA can be chemically modified to become immune‐silent and increase protein expression, LNPs can still trigger innate immune responses and cause inflammation‐related adverse effects. Inflammation can in turn suppress mRNA translation and reduce the therapeutic effect. Dexamethasone (Dex) is a widely used anti‐inflammatory corticosteroid medication th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 56 publications
(117 reference statements)
1
18
0
Order By: Relevance
“…Examination of the tissue sections did not indicate induction of inflammation nor alterations from normal tissue architecture after polyplex treatment (Figure A). LNP administration has been shown to induce proinflammatory responses, owing to the use of ionizable lipids, and strategies have been developed to reduce this effect. , We analyzed the plasma proinflammatory cytokine levels using an ELISA following polyplex treatment. IL-6 and TNFα and were not significantly increased compared to the PBS control, which demonstrated the lack of proinflammatory responses generated by the polyplexes (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Examination of the tissue sections did not indicate induction of inflammation nor alterations from normal tissue architecture after polyplex treatment (Figure A). LNP administration has been shown to induce proinflammatory responses, owing to the use of ionizable lipids, and strategies have been developed to reduce this effect. , We analyzed the plasma proinflammatory cytokine levels using an ELISA following polyplex treatment. IL-6 and TNFα and were not significantly increased compared to the PBS control, which demonstrated the lack of proinflammatory responses generated by the polyplexes (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in line with the scope expansion of the RNA technology, identifying optimal product characteristics for a given route of administration, therapeutic field, or targeted organ will be crucial. While the optimal immunogenic profile and LNP morphology are both likely to be highly variable, targets for other CQAs could also vary [46]. Among others, while neutral particle surface is desired in current RNA vaccine, surface charge appears to be a crucial parameter in organ targeting and in determining lymph node-and mucus-penetrating ability [47][48][49].…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…Additionally, Ndeupen et al reported that robust neutrophil infiltration was found in muscle tissue 24 hours after intramuscular injection of the LNP [178]. This inflammatory response is considered as the causes for the side effect of vaccines and possibly reduce the efficacy to induce the adaptive immunity [179]. Zhang et al reported that an anti-inflammatory (dexamethasone incorporated) luciferase mRNA-loaded LNP showed improved luciferase protein expression compared to conventional LNPs [179].…”
Section: Pd Analysis Using Imaging Lnpmentioning
confidence: 99%
“…This inflammatory response is considered as the causes for the side effect of vaccines and possibly reduce the efficacy to induce the adaptive immunity [179]. Zhang et al reported that an anti-inflammatory (dexamethasone incorporated) luciferase mRNA-loaded LNP showed improved luciferase protein expression compared to conventional LNPs [179]. Therefore, careful assessment of the immune response by LNPs should be conducted during the development of LNP-based platforms [178,180].…”
Section: Pd Analysis Using Imaging Lnpmentioning
confidence: 99%